Judicial Valuation of Damages and Losses - Osterling Parodi, Felipe (1968)
This article analyzes the valuation of damages in the Peruvian legal system. In this framework, it is established that this evaluation can be divided into three forms: the judicial, the conventional and the legal, noting that they have similarities and differences among them. After that, the author focuses on the judicial valuation of damages, especially on the problems that are present in this process. As can be seen, three complex cases can be found in judicial field. First, whether it is necessary to distinguish between the fault and the intent of the debtor in determining the damages and the loss for the breach of the obligation, or whether the same criteria should be applied in both cases. Secondly, what are the effects of the damages that are or can be provided for in the Peruvian Civil Code, and what are their consequences? Finally, whether the concepts of foresight and unforeseeability are synonymous with the cause of the damage or, on the contrary, refer to its amount. In this context, the author presents his point of view and the possible treatment of each of these questions in order to allow a better judicial assessment of damages at the national level.